The Impact of Authentic Materials on Business English Students' Interpretive Reading Comprehension - Himala Praptami Adys (Journal of Innovative and Creativity, 2025)
Business English communication students face significant challenges in developing interpretive reading comprehension skills when using traditional textbook materials that lack real-world business context and authenticity. This study investigates the effectiveness of authentic business materials in enhancing interpretive reading comprehension among Business English communication students, specifically examining their ability to understand and express comprehension of complex business texts. A quantitative research approach was employed with 50 Business English communication students as participants. The study utilized authentic business materials including annual reports, business correspondence, market analyses, and corporate communications. Data collection involved pre-and post-intervention assessments measuring interpretive reading comprehension levels and students' ability to express textual understanding. Results demonstrate that 85% of students achieved correct and comprehensive text understanding when exposed to authentic materials. While students showed proficiency in answering interpretive-level questions, variations existed in their ability to articulate comprehensive reading comprehension across the sample. The findings suggest that authentic materials significantly enhance interpretive reading skills in Business English contexts, though individual differences in expression abilities require targeted pedagogical interventions. This research contributes to ESP (English for Specific Purposes) pedagogy and offers practical insights for curriculum development in business communication programs.